Sistem Informasi Manajemen Proyek Konstruksi Pada CV. Lumbung Agroendo - Mawaddah, Muthia; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2023)
Lumbung Agroendo is a private company in Jambi City. For now, the company has not used information systems effectively, because the data processing is not digital yet. Construction Project Management Information System Design at CV. This Agroendo barn uses the PHP programming language and uses object-based modeling techniques to describe the analysis and design of the system, namely in the form of use case diagrams, class diagrams, and activity diagrams. The output of this research is in the form of a prototype design system for Analysis and Design of Construction Project Management Information Systems at CV. Lumbung Agroendo For further research, it can be complemented with other data management.